PROCESSING RICE HUSK WASTE INTO CHARCOAL AS A PLANT GROWING MEDIUM AND ORGANIC FERTILIZER: PENGOLAHAN LIMBAH SEKAM PADI MENJADI ARANG SEKAM SEBAGAI MEDIA TANAM TUMBUHAN DAN PUPUK ORGANIK - Ida Hasmita; Eka Marya Mistar; Nadia Putri Mauliza; Muhammad (PT. ROCE WISDOM ACEH, 2025)
Cot Puklat Village is a village located in Mukim Melayo where the rice farming profession is the main livelihood for the community. The extensive community rice fields in the village cause husk waste to accumulate after each harvest period, because the utilization of rice husk waste is still very minimal. This is the background for choosing the location of community service activities. This activity aims to socialize to the community about the utilization of rice husk waste into husk charcoal as organic fertilizer and plant media in Cot Puklat Village, Blang Bintang District, Aceh Besar Regency. The community service team (PkM) consists of five lecturers and 10 students majoring in Chemical Engineering, Universitas Serambi Mekkah. This training teaches the community to produce husk fertilizer from rice husk waste in order to provide benefits to the community in increasing the livelihood of the Cot Puklat village community. The community was very enthusiastic in participating in this community service activity. This activity is expected to be able to contribute and play an active role in creating a beautiful, beautiful, and healthy environment, especially in the Cot Puklat Village environment